Arthroscopic tendon release for iliopsoas impingement after primary total hip arthroplasty: a retrospective, consecutive series. Issue 1 (January 2021) - Tassinari, Enrico; Castagnini, Francesco; Mariotti, Federica; Biondi, Federico; Montalti, Maurizio; Bordini, Barbara; Traina, Francesco
Introduction: Aim of this study was to describe the clinical outcomes of 16 patients with iliopsoas (IP) impingement after primary total hip arthroplasty (THA), treated with an arthroscopic tendon release. Methods: 16 patients (11 females/5 males), with a mean age of 57.8 ± 11.1 years (age at THA: 54.4 ± 11 years) and a diagnosis of IP impingement after primary THA, were treated with the Wettstein tenotomy. Preoperatively, every patient underwent a diagnostic ultrasonography guided peritendinous injection and a computed tomography (CT) scan. Every patient was clinically evaluated using WOMAC score. Subjective pain relief and active hip flexion strength were measured. Results: No complications related to arthroscopy were detected. Every cup was prominent with a mean axial overhang of 13 ± 4.8 mm (range 5–20 mm). At a mean follow-up of 27 ± 20.1 months (range 6–48 months), the WOMAC score was 83.7 ± 10.1 points. 13 patients out of 16 (81.3%) had a complete pain relief. 14 patients out of 16 (88%) regained full active hip flexion strength at the final follow-up. 1 patient was scheduled for cup revision after 6 months, due to persistent symptomatology. No demographic data or CT measurements about cup position statistically influenced the outcome. Conclusions: When preceded by an appropriate diagnosis, arthroscopic tenotomy proved safe and effective for IP impingement, regardless the magnitude of cup protrusion.